Correction: Hypoxia inducible factor (HIF) as a model for studying inhibition of protein–protein interactions. Issue 7 (6th June 2017) - Burslem, George M.; Kyle, Hannah F.; Nelson, Adam; Edwards, Thomas A.; Wilson, Andrew J.
Abstract : Correction for 'Hypoxia inducible factor (HIF) as a model for studying inhibition of protein–protein interactions' by George M. Burslem et al., Chem. Sci., 2017, DOI: ; Web:10.1039/c7sc00388a .